2019
DOI: 10.1021/acs.accounts.8b00643
|View full text |Cite
|
Sign up to set email alerts
|

Differential Drivers of Antimicrobial Resistance across the World

Abstract: Conspectus Antimicrobial resistance (AMR) is one of the greatest threats faced by humankind. The development of resistance in clinical and hospital settings has been well documented ever since the initial discovery of penicillin and the subsequent introduction of sulfonamides as clinical antibiotics. In contrast, the environmental (i.e., community-acquired) dimensions of resistance dissemination have been only more recently delineated. The global spread of antibiotic resistant bacteria (ARB) and antibiotic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
130
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(140 citation statements)
references
References 66 publications
0
130
1
9
Order By: Relevance
“…After malaria, typhoid fever is the second most commonly reported disease in Cameroon by health personnels [3]. But the situation is all the more worrying as batrerial strain have been developing resistance to antibiotics (ampicillin and phenicolates) present on the market in recent years [4]. In addition, during salmonella infection, or following exposure of the body to exogenous toxins, the production of free radicals such as superoxide anion and nitric oxide (O 2 -, NO.…”
Section: Introductionmentioning
confidence: 99%
“…After malaria, typhoid fever is the second most commonly reported disease in Cameroon by health personnels [3]. But the situation is all the more worrying as batrerial strain have been developing resistance to antibiotics (ampicillin and phenicolates) present on the market in recent years [4]. In addition, during salmonella infection, or following exposure of the body to exogenous toxins, the production of free radicals such as superoxide anion and nitric oxide (O 2 -, NO.…”
Section: Introductionmentioning
confidence: 99%
“…1.5x10 6 1.9x10 6 --3.5x10 6 3.0x10 6 --9 2.0x10 7 2.4x10 7 --8.0x10 6 7.4x10 6 4.0x10 6 4.3x10 6 10 1.0x10 3 1.6x10 3 --5.2x10 6 5.9x10 6 1.1x10 3 1.0x10 3 11 1.8x10 3 1.3x10 3 --3.2x10 4 2.9x10 4 1.1x10 2 1.0x10 2 12 2.4x10 3 2.8x10 3 --2.5x10 5 2.8x10 5 1.0x10 2 -13 3.1x10 3 2.7x10 3 --1.5x10 3 1.1x10 5 1.0x10 2 1.1x10 2 14 -->300 >300 ----15 -->300 >300 ----16 -->300 >300 ----17 -->300 >300 ----1: EMB agar-(absence of colonies) 2: MacConkey agar In this case, E. coli is the most abundant bacterium with a growth average of 7.7x10 6 CFU/g. Studies carry out by [23], in which analyzes the quantity of Enterobacteria present in waste water treatment plants of milk industry, show that the most abundant bacterium is also E. coli, with an average of 2.6x10 7 CFU/g.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Although bacterial resistance is attributed to purely natural processes due to the ability of bacteria to transfer their genes, it is also true that some inadequate procedures such as incomplete treatment, incorrect doses of antibiotic. Some studies reported that the emergence of resistance to third-generation cephalosporins and carbapenems in Gram-negative isolates might even appear due to the influence of adverse environmental conditions; promote morpho-physiological alterations and expression of genes to guarantee the survival of these microorganisms [3]. The survival of bacteria in other environments depend, however, on many parameters, such as temperature, humidity, pH, soil composition and the presence of the other microorganisms [3].…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater treatment plants (WWTPs) are also key hotspots a liated with the fecology of pathogens and the dissemination of emerging superbugs. These niches are considered as reservoirs of nutrients and/or abundance of elevated bacterial numbers as well as sub-toxic levels of antibiotics favorable for the survival of ARB [15,16]. Reports have revealed the implications of the reuse of treated wastewater nal e uent for irrigation purposes in farms, likewise, a rise of soil microbial biomass as a result of wastewater irrigation was observed in many studies [17][18][19].…”
Section: Introductionmentioning
confidence: 99%